Non-rigid parts inspection by virtual clamping method with simulated displacements - Rosa, Pablo Antunes da (2019)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Mecânica, Florianópolis, 2019.